2017
DOI: 10.13057/biodiv/d180126
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of red and black upland rice accessions from East Nusa Tenggara, Indonesia as revealed by agro-morphological characters

Abstract: Abstract. Firawati I, Murwantoko, Setyobudi E. 2017. Morphological and molecular characterization of hairtail (Trichiurus spp.) from Indian Ocean, southern coast of East Java,. The objective of this study was to identify species of hairtails (Trichiurus spp.) which caught from the southern coast of East Java, based on morphology and molecular characters. Three hundred and forty-nine fish samples were collected from two fishing port i.e. Muncar and Prigi. Twenty-two morphometric and four meristic characters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Based on the principal component analysis (PCA), distinguishing characters to differentiate Pangandaran's hairtail were caudal peduncle and parts around the body. The previous study reported that the characteristics to differentiate T. lepturus from T. brevis in Prigi and Muncar were located in the head and tail [4]. Moreover, the discriminant analysis showed that meristic characteristics of upper jaw length and caudal peduncle length can also be used.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the principal component analysis (PCA), distinguishing characters to differentiate Pangandaran's hairtail were caudal peduncle and parts around the body. The previous study reported that the characteristics to differentiate T. lepturus from T. brevis in Prigi and Muncar were located in the head and tail [4]. Moreover, the discriminant analysis showed that meristic characteristics of upper jaw length and caudal peduncle length can also be used.…”
Section: Discussionmentioning
confidence: 97%
“…Based on morphological and molecular analysis, there are only two species i.e. T. lepturus and T. brevis were found at the Indian Ocean Southern coast of East Java [4]. T. lepturus has a very broad geographical distribution, covers tropical and temperate waters throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…Phapumma et al (2020) reported that plants with a tall appearance are not favorable traits for grain yield. Plants with a semi-dwarf performance are more desirable than tall ones because semi-dwarf plants are stronger in facing environmental factors such as wind and rain (Mau et al 2017;Hermanasari et al 2021). Hence semi-dwarf plant height becomes an essential trait for the breeder in the rice improvement program.…”
Section: Growth Flowering and Yield Performancementioning
confidence: 99%
“…Comprehensive knowledge of genetic availability and diversity is needed for crop improvement and the future development of new high-yielding varieties (Malek et al 2014;Adie and Krisnawati 2017;Weerakoon and Somarate 2021). The study of genetic diversity in local upland rice cultivars based on agro-morphological traits can provide reliable information for selection and further work on producing new superior varieties (Mau et al 2017). The higher variability of, the traits the immense opportunity to obtain the desirable traits and candidate as a new potential cultivar.…”
Section: Introductionmentioning
confidence: 99%
“…Thousands of SSR markers were developed for rice research studies (Huggins et al 2018). It has been used for molecular characterization, population structure, genotypic identification, and genetic variability estimations (Mau et al 2017;Islam et al 2018). Furthermore, it has also proven useful for linkage maps construction, gene mapping, MAS (Gonzaga et al 2015) and diversity studies (Rashimi et al 2017).…”
Section: Introductionmentioning
confidence: 99%